Efektivitas hafalan Al-Qur'an metode pisah sambung terhadap peningkatan prestasi belajar pada anak-anak Sekolah Dasar. - Nadira Sofwatunnisa R (FKU 13 UMY 440, 2013)
Learning process sometimes have problems such as low memory causing decreased learning achievement. Memorizing the Holy Qur'an train student to memorize . One method is a method of separating memorize continued. This study aims to determine the effectiveness of the Holy Qur’an memorization with separating connecting methods to increase learning achievement in elementary school student. This study used a quasi-experimental, case control. The samples were the 3rd grade students with total sampling technique. 34 students from 3A grade as control group and 34 students from 3B as test group. Both sample groups have carried out pre-test and post-test. Intervention of test group is Al Quran memorizing for 15-20 minutes/day before starting learning activities in class for 2 months. Learning achievement is assessed by comparing the mean value of posttest score. The data are analyzed using Independent T test. The mean results of post-test in control group is 75.8±9.9 and test group is 7.74±9.9.The comparison of post-test results between control and test groups p=0.504 show no significant changes of learning achievement. It can be concluded that memorizing of Qur'an with separating connecting method isn’t effective to increase learning achievement of student in SDN1 Bangunjiwo. Keywords: learning achievement, memorizing, the Holy Qur'an.